Escherichia coli with virulence factors and multidrug resistance in the Plankenburg River - Lamprecht, Corne; Romanis, Marco; Huisamen, Nicola; Carinus, Anneri; Schoeman, Nika; Sigge, Gunnar O.; Britz, Trevor J. (South African Journal of Science, 2014)
Escherichia coli is a natural inhabitant of the gut and E. coli levels in water are considered internationally to be an indication of faecal contamination. Although not usually pathogenic, E. coli has been linked to numerous foodborne disease outbreaks, especially those associated with fresh produce. One of the most common ways through which E. coli can be transferred onto fresh produce is if contaminated water is used for irrigation. In this study, a total of 81 confirmed E. coli strains were isolated from the Plankenburg River as part of three separate studies over 3 years. During sampling, E. coli levels in the river were above the accepted levels set by the World Health Organization and the South African Department of Water Affairs and Forestry for safe irrigation of fresh produce, which indicates that transfer of E. coli during irrigation is highly probable. Multiplex polymerase chain reaction screening for pathogenic gene sequences revealed one enteroaggregative positive strain and four enteropathogenic positive strains. The four enteropathogenic strains were also found to be resistant to three or more critically and highly important antibiotics and were therefore classified as multidrug resistant strains. These results show that E. coli with enteropathogenic potential and multiple antimicrobial resistance properties has persisted over time in the Plankenburg River.